Planktonsukzession und Produktionsvorgänge in zwei Auskiesungsseen am mittleren Main - Aguirre Ramirez, Nestor Jaime; Justus Liebig University Giessen (My University, 1999)
During one year, a study on plankton dynamics on two lakes located on the alluvial plain of the Main river was performed. Every month, data of the mostimportant physical, chemical and biological factors were gathered. Based on this, the question on which factors influence plankton succession in both lakes wasanswered. Lake 1 (Main-km 314.75) has a surface of 10.6 ha and an average depth of about 1 m. This lake is connected with the Main river through an overflow pipe,whereby massive water exchange with the river occurs only during the high water period. Lake 2 (Main-km 310) has a surface of 9.5 ha and an average depth of about 3 m. This lake has a connection with the Main river through a channel, by meansof which there is a continuous water exchange throughout the year. The main difference between the two lakes lies basically on the massive water exchangebetween the Main river and both lakes, whereby water exchange in lake 1 does not occur during most part of the year, while in lake 2. it occurs constantly.Besides this, it was found that lake 2 showed an irregular bathymetric profile, a maximum depth of 6.2 m and a water volume about three times larger than thatof lake 1. The two lakes are polymictic showing orthograde temperature profiles during the cold months of the year and a tendency to stratification in summer during theday with nocturnal circulation. Due to frequent water mixture, there was a substance homogenization in the water column. In both lakes, phosphorus was not found to be the limiting factor, due to permanent water circulation and iron dynamics. In lake 1 algae growth was limited bylow nitrogen availability. Consequently, populations of nitrogen-fixing blue-green algae settled, especially in August and September, whereby a tendency toeutrophication of the lake was evident. In lake 2, due to a continuous water exchange with the Main river, eutrophication was more regulated. In this lake, aCyanphyceae bloom was not observed. The phytoplankton diversity index in lake 1 showed strong variation throughout the year with high values in June and July. This index displayed a highcorrelation with the dominance degree and population equitability. Lake 2 exhibited low diversity index values and small variation with time, correlated mainlywith the dominance degree of species. In both lakes the zooplankton diversity index showed low values and little variation with time. In lake 1 a high correlation between this index, equitability anddominance degree was found. In lake 2 the zooplankton diversity index was found to be highly correlated with dominance degree. Overflow of the river duringwinter caused massive water exchange with the two lakes. The difference in plankton succession between both lakes was principally characterized by waterexchange of lake 2 with the Main river throughout the year, while lake 1 functioned as a closed system. In both lakes plankton succession was characterized bya high alternation of populations and absence of species coexistence. In total 141 phytoplankton species and 26 zooplankton species were determined. Though a high species number was observed, the diversity index valuescalculated for each month were low. This was caused by a high influence of dominant species in each month and species alternation during the year.
Keywords: ddc:570